TICKS AWAY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Brother Herman van Waes, Boende, Zaire, referring to the question in the French edition of Spore 63 on tick control methods other than soaking: 'There is another way. For the last ten years, we have injected our cattle and sheep with Ivomec...